Genipa americana L. GEOGRAPHIC OCCURRENCE IN BRAZIL - Cola, Raquel Elvira; Gonçalves, Maria da Penha Moreira; Gallo, Ricardo (Floresta, 2022)
Genipa americana is a well-recommended tree species for the restoration of degraded areas, and it is necessary to understand which soil and climate variables determine its occurrence and in which environments it would become better adapted. The objective of this work was to survey the occurrence of Genipa americana in Brazil and the edaphoclimatic and vegetation variables' influence on its distribution. For this, the survey was carried out using the NeoTropTree database, using 19 environmental variables for the study. The data were submitted to principal component analysis in RStudio, with the factoextra and ggplot2 packages. The main variables from this analysis were applied in the map elaboration with the ArcMap 10.5 program. In the geographic occurrence analysis of 3,916 site results for Brazil, the species G. americana was present in 20.9% of the sites. The predominant biome in the species occurrence in the country was the Amazon, concentrating 38.9% of the sites. Regarding environmental limits, it is clear that the lower the temperature, the lower the chance of the species occurrence. The species is well adapted to high temperatures, annual rainfall ranging from 1,000 to 2,500 mm, and low reliefs. With climate change imminent, it could be used to restore warm regions. However, sites currently dry or threatened with becoming more arid over the years are unsuitable for the species.